The Effect Of Dzikir On Reducing Anxiety Levels In Pre-Cataract Surgery Patients At The Puri Cinere Hospital Eye Clinic - Supriyanti, Lily; Susanti, Dewi; Trisna, Eva (Jurnal EduHealth, 2024)
Cataract is the occurrence of clouding in the lens of the eyeball which causes decreased visual ability to the point of blindness. One measure to prevent cataracts from causing blindness is surgery. Surgery or operations often cause anxiety in patients before surgery. Non-pharmacological therapy that can reduce anxiety levels in preoperative patients is dzikir. This study aims to determine the effect of dzikir on reducing anxiety levels in pre-cataract surgery patients at the Puri Cinere Hospital Eye Clinic. This research uses a quasi-experimental research design, one group pretest and posttest design without control. The population in this study were all patients who would undergo cataract surgery at the Puri Cinere Hospital Eye Clinic with a total sample of 18 people. The sampling technique is purposive sampling. The instrument of this research is the HARS questionnaire. Statistical tests use the Wilxocon test. The results of the study showed that the anxiety level of pre-cataract surgery patients at Puri Cinere Hospital Eye Clinic before the Dzikir was carried out, the majority experienced moderate anxiety, 11 respondents (61.1%) and after the Dzikir the majority had no anxiety, 14 respondents (77.8%). The results of the Wilxocon test showed that there was an effect of Dzikir on reducing anxiety levels in pre-cataract surgery patients at the Puri Cinere Hospital Eye Clinic with a p-value = 0.000. It is hoped that the results of this research can provide input for the nursing field in the non-pharmacological management of patients who experience anxiety before cataract surgery.